Juridical Analysis of the Implementation of the Self-Assessment System within the Framework of Indonesian Tax Law on the Obligations of Individual and Corporate Taxpayers - Rizq Rafi Rabbani (JURNAL MAHASISWA YUSTISI, 2026)
The success of tax collection is not only determined by the magnitude of tax potential but also by the effectiveness of the collection system implemented and the level of taxpayer compliance in fulfilling their obligations. This system grants taxpayers the authority to calculate, account for, pay, and report their own owed taxes based on the provisions of the legislation, as regulated in Law Number 6 of 1983 and its amendments. The research method used is normative juridical with a legislative and conceptual approach. The research results show that the implementation of the self-assessment system has been functioning as the main system in tax collection in Indonesia and has been able to improve administrative efficiency and taxpayer participation. However, its effectiveness in improving compliance still faces various obstacles, such as low material compliance, regulatory complexity, and limited taxpayer understanding. The differences in characteristics between individual taxpayers and corporate entities also affect the level of compliance. Furthermore, supervision and law enforcement by tax authorities have not yet been fully optimal. Strengthening regulations, improving tax literacy, and optimizing information technology are strategic steps to enhance the effectiveness of this system.